Discussions on the nature of research in psychoanalysis - Azcona, Maximiliano (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2018)
This article review the main perspectives of research in the psychoanalytic field and aims to give support to the following conjectures: (I) the appeal to some epistemological and methodological criticisms has been a key factor to justify the development of extra-clinical research in the interior of the psychoanalytic field, and (II) the dismissal of the case study methodology is held under some budgets which deserve to be reviewed and discussed.It is concluded the need to amplify this type of meta-theoretical discussions on the modes of production of knowledge in psychoanalysis.